1976
DOI: 10.1007/bf00426832
|View full text |Cite
|
Sign up to set email alerts
|

Single and repeated administration of neuroleptic drugs to rats: Effects on striatal dopamine-sensitive adenylate cyclase and locomotor activity produced by tranylcypromine and L-tryptophan or L-dopa

Abstract: Injection of tranylcypromine and L-tryptophan results in rats displaying behavioural changes including hyperactivity, probably due to stimulation of post-synaptic 5-hydroxytryptamine (5-HT) receptors. Increased locomotor activity of a different type is elicited by injection of tranylcypromine and L-dopa, a procedure which increased dopaminergic function in the brain. It has now been demonstrated that the neuroleptic drugs, chlorpromazine, alpha-flupenthixol, haloperidol and spiroperidol block both syndromes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Sloviter, Drust & Connor (1978) have recently argued against this on the basis of the failure of both pimozide and oc-methyl-p-tyrosine pretreatment to attenuate the response. However, it had already been shown that pimozide did not inhibit the 5-HT-mediated behavioural response, in marked contrast to a whole range of other neuroleptics (Heal, Green, Boullin & Grahame-Smith, 1976) and indeed does not appear to inhibit dopamine-sensitive adenylate cyclase either in vitro (Clement-Cormier, Kebabian, Petzold & Greengard, 1974) or in vivo (Heal, Green, Bloomfield & Grahame-Smith, 1978). Table 3 Results expressed as mean ± s.d.…”
Section: Resultsmentioning
confidence: 95%
“…Sloviter, Drust & Connor (1978) have recently argued against this on the basis of the failure of both pimozide and oc-methyl-p-tyrosine pretreatment to attenuate the response. However, it had already been shown that pimozide did not inhibit the 5-HT-mediated behavioural response, in marked contrast to a whole range of other neuroleptics (Heal, Green, Boullin & Grahame-Smith, 1976) and indeed does not appear to inhibit dopamine-sensitive adenylate cyclase either in vitro (Clement-Cormier, Kebabian, Petzold & Greengard, 1974) or in vivo (Heal, Green, Bloomfield & Grahame-Smith, 1978). Table 3 Results expressed as mean ± s.d.…”
Section: Resultsmentioning
confidence: 95%
“…For instance, catecholamines have been suggested to have a role (Deakin & Green, 1978); reserpinised rats fail to exhibit some behavioural effects of 5-HT receptor stimulation (Tricklebank et al, 1984) and dopamine antagonists attenuate the syndrome (Heal et al, 1976). Squires & Lassen (1975) suggested that the syndrome may be dependent on N-substituted derivatives of 5-HT which are partly deaminated by MAO-B.…”
Section: Introductionmentioning
confidence: 99%
“…This does not appear to be due to the dopamine receptor blocking action of this drug as several other neuroleptics examined (haloperidol, spiroperidol and a-flupenthixol) do not have this action (Heal et al, 1976). It seems probable that the enhancement is due to blockade of 5-HT receptors by chlorpromazine.…”
Section: Discussionmentioning
confidence: 89%
“…Since it has been demonstrated previously that the 5-HT hyperactivity syndrome is mediated via a postsynaptic dopaminergic system (Green & GrahameSmith, 1974) the question arises as to why repeated administration of other neuroleptics, which demonstrably increase dopaminergic sensitivity (Heal et a., 1976) does not result in increased 5-HT responses. No definitive answer can yet be given to this but it seems reasonable to suppose that transmitter interactions are modulatory and some alteration in the sensitivity of a dopaminergic system need not result in changes in 5-HT function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation